2010
DOI: 10.4300/jgme-d-10-00028.1
|View full text |Cite
|
Sign up to set email alerts
|

Quality Education and Safe Systems Training (QuESST): Development and Assessment of a Comprehensive Cross-Disciplinary Resident Quality and Patient Safety Curriculum

Abstract: Background Over the past decade, regulatory bodies have heightened their emphasis on health care quality and safety. Education of physicians is a priority in this effort, with the Accreditation Council for Graduate Medical Education requiring that trainees attain competence in practice-based learning and improvement and systems-based practice. To date, several studies about the use of resident education related to quality and safety have been published, but no comprehensive interdisciplinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Undergraduate medical students and postgraduate trainees still must acquire their PS knowledge through informal education in hospitals because formal training of patient safety curricula is lacking. 4 A WHO curriculum guide is developed to help medical schools to develop their own patient safety curriculum. 5…”
Section: Introductionmentioning
confidence: 99%
“…Undergraduate medical students and postgraduate trainees still must acquire their PS knowledge through informal education in hospitals because formal training of patient safety curricula is lacking. 4 A WHO curriculum guide is developed to help medical schools to develop their own patient safety curriculum. 5…”
Section: Introductionmentioning
confidence: 99%
“…10,[16][17][18][19][20][21][22][23][24][25] Yet, implementation of safety education programs has been variable and many residents and faculty remain with little or no formal training in these concepts. 7,9,23,26,27 In 2006, the University of Michigan implemented a Patient Safety Learning Program (PSLP) in its internal medicine and medicine-pediatrics residency training programs. Recognizing we had few qualified faculty members, 23,[28][29][30] few ''formal'' learning experiences, 7,8,23,24 and limited precedent for resident-driven safety and quality projects, we defined 3 primary goals for our PSLP: (1) to teach residents key patient safety concepts; (2) to transform our cultural environment; and (3) to provide experiential opportunities for residents to apply the patient safety and quality improvement concepts.…”
Section: Methodsmentioning
confidence: 99%
“…Results: Our updated search identified 699 additional articles, 16 of which met criteria for inclusion. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Combined with studies identified in the original systematic review, there are now 40 published QI&PS curricula that target postgraduate trainees, 30 of which report an evaluative component. Table 1 summarizes emerging trends in QI&PS training.…”
Section: Contributors: Michelle Thompson MD and Christine M Raup mentioning
confidence: 99%